Dissecting Selective Translation of HSP90 mRNA in Mammalian Cells - Shaikho, Sarah (Université d'Ottawa / University of Ottawa, 2016)
Mammalian Hsp90 is a ubiquitous molecular chaperone that undergoes selective translation under stress. However, the precise control mechanism of HSP90 translation is yet to be elucidated. Polysome profiling has revealed that HSP90α mRNA is selectively translated, although global translation is inhibited during heat shock. A genetic screen identified two ribosomal proteins, RPL36A and RPL42, as translation regulators of yeast HSP90. I found that knockdown of either RPL36 or RPL36A, mammalian homologs of the yeast ribosomal proteins, modulates HSP90α expression under basal and heat shock condition, suggesting that the selective translation mechanism is conserved between humans and yeast. Profile expression in rhabdomyosarcoma cell line revealed a correlation between HSP90 protein levels and RPL36/RPL36A expression, suggesting that they might be the drivers behind elevated HSP90 expression. Interestingly, a higher level of RPL36 and RPL36A rendered cells less sensitive to HSP90 inhibitor, suggesting that they may be predictors of HSP90 inhibitor resistance.
Keywords: HSP90